BRATA DALAM GEGURITAN SALAMPAH LAKU KARYA IDA PADANDA MADE SIDEMEN - Putu Eka Guna Yasa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
This paper discusses the types and benefits of brata in one of the literary works written by Ida Padanda Made Sidemen entitled Geguritan Salampah Laku. Methodologically, this study starts from the stage of providing data followed by data analysis to presenting the results of data analysis. At the data provision stage, the literature method is used, namely collecting primary data in the form of lontar manuscripts collected by the Pusat Dokumentasi Kebudayaan Bali and secondary data in the form of an appendix to the assessment of Geguritan Salampah Laku. At the data analysis stage, a qualitative descriptive analysis method was used which was supported by the Semiotic theory to reveal more clearly the types and benefits of the brata contained in Geguritan Salampah Laku. The results of the data analysis are presented using ordinary or informal words so that readers can know and even practice them practically. Based on the study conducted on Geguritan Salampah Laku, it can be seen that brata has been discussed from the beginning, middle, to the end of the literary work. In the first part, there is brata amaṅun puasa sawĕguṅ which is performed by Ida Padanda Made Sidemen by eating only once a day. The benefits of brata are closely related to the success of the learning process undertaken by Ida Padanda Made Sidemen in the learning process at Gria Mandara, Sidemen, Karangasem. Furthermore, Geguritan Salampah Laku also explained brata in general through Ida Padanda Nabe's message to Ida Padanda Made Sidemen. The benefit of doing brata for a priest is the success of the chanting mantras as well as changing the quality of human birth (yoni) in the next life. At the end, Geguritan Salampah Laku also contains brata rahina tan suptāturu or not sleeping while the sun is still rising and working for life. The benefits of brata are actually the key behind Ida Padanda Made Sidemen's creativity in creating various works, both in the form of literature, sculpture, and architecture whose usefulness can still be felt today